Zinc use efficiency of maize-wheat cropping after inoculation with Azospirillum brasilense - Galindo, Fernando Shintate; Miranda Bellotte, Joao Leonardo [UNESP]; Kondo Santini, Jose Mateus [UNESP]; Buzetti, Salatier [UNESP]; Leonel Rosa, Poliana Aparecida [UNESP]; Jalal, Arshad [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP] (Springer, 2021)
Sustainable zinc (Zn) management strategies are needed to improve cereal yield production, particularly under tropical savannah conditions. Inoculation with plant growth-promoting bacteria, such as Azospirillum brasilense, could be a useful and sustainable strategy to enhance agronomic Zn use efficiency (AZnUE), leading to better cereal development. This study was developed to explore the effect of seed inoculation with A. brasilense combined with Zn application rates on maize-wheat crop development, AZnUE and grain yield. The field experiments were conducted during four cropping seasons, using five Zn application rates (0-8 kg Zn ha(-1)), with maize grown in the first season, and two seed inoculation treatments (without or with A. brasilense) applied to both maize and wheat crops. Our results showed that inoculation was effective in promoting maize and wheat development with higher AZnUE (an increase of 76% and 17% for maize and wheat, respectively), leading to a greater yield (an increase of 6% for the maize and wheat harvests). The estimated applied Zn rates (between 4 and 5 kg Zn ha(-1)) resulted in higher maize-wheat grain yields. Our study explored new perspectives of A. brasilense inoculation related to nutrient uptake and use efficiency under different seasonal climatic conditions. First, we examined the positive effect of A. brasilense on maize and wheat Zn uptake and AZnUE in tropical Zn-deficient soils. In addition, we examined the positive effect of A. brasilense inoculation on maize and wheat development and grain yield under harsh climatic conditions such as in the Brazilian savannah.
Keywords: Zinc fertilization; Plant growth-promoting bacteria; Tropical soil; Cereal grain production; Nutrient management strategies